Pertimbangan Biaya dalam Pemilihan Bekisting - Mohammad Arif Bahtiar Efendi; Rendi Gusta Wibowo (JURNAL PILAR TEKNOLOGI Jurnal Ilmiah Ilmu Ilmu Teknik, 2021)
Materials in the construction world is progressing quite rapidly. Likewise formwork as a project is also experiencing quite rapid progress which refers to the value of the results of a project. In a project the determination of the type of system and formwork method will affect the cost and time in progress, the selection of the formwork method which is not appropriate will have a loss in the future. The analysis conducted is comparing formwork of semi-conventional methods and system (PERI) in column, beam and plate formworks of the INKA Graha Building Construction Project, Madiun. The objective to be achieved in this paper is to find out the type of formwork that is efficient to be used in a formwork work both for beam and plate columns, in terms of cost comparisons and finding a draw point between the two methods. After analyzing it is known that the use of semi-conventional initiating systems is more efficient with a value of Rp. 2,349,756,391, - and for the PERI system costs Rp. 3,050,649,782, - .. The draw point of this system is in the volume of 31,500 m2 which means that in this volume the use of semi-conventional systems and PERI systems does not differ in terms of cost.